Anti-cryptojacking system - Goh, Asher Ashley Ghin Shi (2025)
This final year project is about creating a browser-based Anti-Cryptojacking System to protect users from hidden mining attacks. Cryptojacking happens when malicious scripts secretly use a person’s computer resources to mine cryptocurrency without permission. The system is developed as a browser extension that can block harmful websites using an updated blacklist, scan webpages for suspicious keywords, functions or scripts, and monitor CPU usage for unusual spikes. It works quietly in the background and alerts users in real time if a threat is detected, while making sure normal browsing is not affected. The extension is built to be lightweight, user-friendly, and easy to install, so even non-technical users can benefit from it. Research for this project involved reviewing current detection tools, studying different prevention techniques, and applying them into a practical extension design. Testing results have shown that the extension can successfully detect and prevent cryptojacking activities, making it a reliable solution for everyday browsing. This project contributes to the field of cybersecurity by providing a simple and effective tool that raises awareness and protects users against cryptojacking attacks.